Peran Pemerintah Kota Tanjungpinang Dalam Penanggulangan Kemiskinan - Yusnike Yusnike; Jupita Natalia (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The Tanjung Pinang City Government has a crucial role in alleviating poverty in its area. This research aims to evaluate the role and steps taken by the local government in an effort to reduce the level of poverty in the city. This study includes an analysis of the policies implemented by the Tanjung Pinang City Government in dealing with poverty problems. The main focus is on social programs, economic initiatives, education, health, and infrastructure development designed to reduce poverty levels in various levels of society. The research methods used include surveys, secondary data analysis, and interviews with relevant stakeholders, including non-governmental organizations, academics, and local government. The collected data is then analyzed to evaluate the effectiveness of the programs that have been implemented and to identify challenges and potential solutions in reducing poverty in Tanjung Pinang. The research results highlight various steps that have been taken by the Tanjung Pinang City Government in an effort to reduce poverty, such as social assistance programs, skills training, access to health and education services, and infrastructure development. However, several obstacles were also identified, such as budget limitations, coordination between institutions, and complex socio-economic challenges that hampered the effectiveness of these programs. This research provides an overview of the role played by the Tanjung Pinang City Government in alleviating poverty. Recommendations are provided for improving and improving strategies, cross-sector collaboration, and increasing resource allocation to increase the effectiveness of poverty reduction efforts in the region.